Beyond Technical Standards: A Competency-Based Framework for Access and Inclusion in Medical Education. (December 2020) - Curry, Raymond H.; Meeks, Lisa M.; Iezzoni, Lisa I.
Abstract : Efforts to include people with disability as students and practitioners in the health professions have gained momentum in recent years. However, prevailing technical standards at U.S. medical schools have biases that can prevent or impede their admission, promotion, and graduation. These standards derive from an approach first promulgated in 1979 and have since remained largely unaltered. Current technical standards at most medical schools are now at odds with changes occurring since the 1990 enactment of broad civil rights protections for people with disability and current aspirations for diversity, equity, and inclusion in the medical profession. It is time to replace the technical standards construct with an approach more consistent with current medical practices, and with societal imperatives of equity and social justice. Such an approach should assess candidates' demonstrable skills and merits, rather than relying on a preconceived construct identifying the presence or absence of defined levels of ability. The maturation of competency-based approaches to curricular design and assessment provides an opportunity to reconceptualize the abilities required to practice medicine, foster the appropriate inclusion of physicians with disability, and better align medical education and training with broader societal needs and goals.